2003
DOI: 10.1080/09553000310001626135
|View full text |Cite
|
Sign up to set email alerts
|

Geldanamycin, an inhibitor of Hsp90, sensitizes human tumour cells to radiation

Abstract: Targeting Hsp90 with GA provides a promising experimental strategy for radiosensitization of carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
48
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 19 publications
5
48
0
1
Order By: Relevance
“…Previous studies have shown that inhibition of Hsp90 enhances the radiation response of several cell lines derived from a variety of human tumour entities (Bisht et al, 2003;Enmon et al, 2003;Machida et al, 2003;Russell et al, 2003;Bull et al, 2004;Harashima et al, 2005;Dote et al, 2006). These findings validate the molecular chaperone Hsp90 as a clinically relevant target for tumour radiosensitisation.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Previous studies have shown that inhibition of Hsp90 enhances the radiation response of several cell lines derived from a variety of human tumour entities (Bisht et al, 2003;Enmon et al, 2003;Machida et al, 2003;Russell et al, 2003;Bull et al, 2004;Harashima et al, 2005;Dote et al, 2006). These findings validate the molecular chaperone Hsp90 as a clinically relevant target for tumour radiosensitisation.…”
Section: Discussionsupporting
confidence: 60%
“…Indeed, a number of studies have already explored Hsp90 as a potential molecular target for radiosensitisation of tumour cells (Bisht et al, 2003;Machida et al, 2003;Russell et al, 2003;Bull et al, 2004;Harashima et al, 2005;Dote et al, 2006;Kabakov et al, 2008;Wu et al, 2009). Thus, the inhibitor of Hsp90, geldanamycin, and its derivatives significantly enhance the radiosensitivity of tumour cell lines derived from a variety of histologies, including glioma, prostate, pancreas and cervix (Bisht et al, 2003;Enmon et al, 2003;Machida et al, 2003;Russell et al, 2003;Bull et al, 2004;Harashima et al, 2005;Dote et al, 2006). However, geldanamycins have several limitations, including poor solubility, formulation difficulties, hepatotoxicity and extensive metabolism by polymorphic enzymes, along with drug efflux by P-glycoprotein (Kelland et al, 1999;Eiseman et al, 2005;Brough et al, 2008;Eccles et al, 2008).…”
mentioning
confidence: 99%
“…Cell survival was measured by a colony formation assay (20). Briefly, cells were seeded in 24-cm 2 flasks and incubated for ~24 h before treatment with scriptaid or TSA.…”
Section: Methodsmentioning
confidence: 99%
“…(46,51) We and others have reported that Hsp90 inhibitor geldanamycin and its less toxic derivative 17AAG sensitizes tumor cells, but not normal cells, to radiation. (52)(53)(54) These findings led us to investigate radiosensitization by 17AAG in multicellular spheroids. Spheroids are tumor cell aggregates growing in a three-dimensional structure that simulate the growth and microenvironmental conditions of in vivo tumors.…”
mentioning
confidence: 99%